Exploring the pretreatment routes of waste printed circuit boards for enhanced metal recovery - Jha R.; Sharma R.; Agrawal M.; Rao M.D.; Singh K.K. (My University, 2025)
Obsolete printed circuit boards (PCBs) have been identified as secondary resources of valuable metals (Au, Ag, Cu, etc.) at the same time environmental contaminants in case of improper dumping, landfilling, and open burning. Therefore, the recycling of waste PCBs is very essential for recovering these metals, maintaining the circular economy, and also for protecting our environment. The present work investigates two pretreatment routes; delamination of waste printed circuit boards (WPCBs) by Dimethylacetamide (DMA) and ultrasonic treatment of milled waste printed circuit boards (WPCBs) for the separation of metallic fractions. Initially, discarded mobile WPCBs are preprocessed and the attached components were removed by a heating gun. Bare WPCBs were shear cut and shortened into 1 × 1 cm2. In the former case, effective delamination of WPCBs has been achieved by DMA at optimized conditions 150◦C, 16 h with a solid-liquid ratio of 3:10. In the later process, downsized WPCBs were fed into the hammer mill to obtain the powder. The Powdered WPCBs were further processed through ultrasonic cleaner to acquire metal-rich fractions. The delaminated metallic fractions, hammer milled powder and ultrasonically separated metallic powder were dissolved into aqua regia to get metal concentration. Moreover, XRD and SEM-EDS analysis revealed that the same metals were present in directly milled, ultrasonically cleaned powder and delaminated metallic fractions. However, an increased weight % of a few metals was observed in the case of ultrasonically cleaned powder and it was further confirmed using ICP-MS and AAS analysis. The current study revealed that the ultrasonic-assisted process is a faster and more cost-effective process. Copyright © 2023 Elsevier Ltd. All rights reserved.